2019
DOI: 10.3390/f10040346
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Synthesis and the Expression Patterns of bHLH Transcription Factor Family during Development of the Chinese Jujube Fruit (Ziziphus jujuba Mill.)

Abstract: The basic helix–loop–helix (bHLH) family is an important transcription factor for eukaryotes and is involved in a wide range of biological activities. Among these, bHLH can interaction with WD repeat (WD40 or WDR) and V-myb avian myeloblastosis viral oncogene homolog (MYB) form a ternary complex to promote the efficient synthesis of anthocyanins. In this study, a total of 138 jujube bHLH (ZjbHLH) family members were screened from the transcriptome of the two jujube cultivars, ‘Junzao’ (JZ) and ‘Tailihong’ (TLH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Prunus amygdalus L.) [ 33 ]. Biosynthetic functions for more bHLH genes will likely be identified [ 34 ].…”
Section: Roles Of Plant Bhlhs In Biosynthetic Processesmentioning
confidence: 99%
“…Prunus amygdalus L.) [ 33 ]. Biosynthetic functions for more bHLH genes will likely be identified [ 34 ].…”
Section: Roles Of Plant Bhlhs In Biosynthetic Processesmentioning
confidence: 99%
“…In this study, we identified 102 bHLH genes in the walnut genome, and their predominantly nuclear localization was in accordance with their function as TFs ( Supplementary Table S3). bHLH genes constitute large families, with 188 members in apple and 138 in jujube (Ziziphus jujuba; Mao et al, 2017;Shi et al, 2019) that can be divided into 15-25 subfamilies (Pires and Dolan, 2010). Our phylogenetic analysis showed that walnut bHLHs formed 15 subfamilies (Supplementary Figure S4A and Figure 3; Heim et al, 2003).…”
Section: Discussionmentioning
confidence: 69%
“…The bHLH TF has been reported to play important roles in plant growth/development, metabolism, and response to stress tolerance (Abe et al, 2003;Pillitteri and Torii, 2007;Zhao et al, 2008;Liu et al, 2013;Shi et al, 2019;Song et al, 2020;Sun et al, 2020). The best-characterized member in this FIGURE 9 | qRT-PCR analysis of the expression patterns of stress-related genes under different stresses in transgenic tobacco lines.…”
Section: Discussionmentioning
confidence: 99%